Household livelihood strategies in the miombo woodlands of Tanzania: emerging trends - Monela, G.C.; Kajembe, G.C.; Kaoneka, A.R.S.; Kowero, G.S. (2001)
The study was undertaken in Tanzania to assess the effect of some macro-economic policies on livelihood strategies for households within or in close proximity in miombo woodlands. The focus was on how their responses are impacting on the management and use of the woodlands. Data were collected at macro level from three sites categories as remote, intermediate and peri-urban. Also data on important macroeconomic trends were collected. The results indicate that reductions government spending have decreased agricultural support in terms of extension services and subsidies on farm inputs. The increase in prices of input factors relative to output has raised costs of farm inputs, cost of living in general and decreased disposable incomes for most rural dwellers, forcing some of them into extensive forest product exploitation and trade for each incomes. in the study sites, some forest products contribute between 50-70% of annual household incomes. However not many households have the capacity to take the advantage of promising forest-based income generating activities. Economic hardships also led to changes in gender roles particularly in per-urban and intermediate sites. Women are increasingly expanding their roles, away from traditional domestic activities to income generating activities such as forest product exploitation and sale, casual labour and petty business. Men are gradually talking up activities which have traditionally been in the domain of women. The role of local institutions and traditional values in management of woodlands has declined. Village governments have replaced village and clan elders in land allocation. Local beliefs of value for forest protection and traditional property rights which influence utilization of communal resources have gradually been eroded. Some macro-economic policies have created conditions for broadening the cash income base of rural communities and have put value on some otherwise non-tradable forest products. Local communicates advocate for the full involvement in the management and use of these resources. .